Ergonomic Evaluation of Manually Operated Single Row Manual Vegetable Transplanter - Kumar, Vinay (Indian Journal of Hill Farming, 2019)
India is the second largest producer of vegetables after China. In India, transplanting of the vegetable seedlings of different crops depend completely on human labour. In changing scenario of agricultural mechanization, ergonomics plays crucial role for effectiveness of the operation. Therefore the study was undertaken to evaluate the single row manual vegetable transplanter on three different types of vegetable crops i.e. brinjal, chilli and tomato at two different sites and compare it with traditional method of transplanting on ergonomic basis and to work out the energy expenditure rate involved in the operation. The activity of work load was classified as moderate with maximum heart rate (112 beats/min) and energy expenditure (9.1 kJ/min) with single row manual vegetable transplanter. The activity of work load was classified as heavy with maximum heart rate (125 beats/min) and energy expenditure (11.15 kJ/min) with traditional method of transplanting. Mean value of overall discomfort rating, musculo-skeletal problem, rating of perceived exertion were also very less in comparison with traditional method of transplanting.